Analisis Fundamental Dan Teknikal Pergerakan Harga Saham Sebelum Dan Saat Pandemi Covid-19 Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Imam Mahrus Afwan Romadhoni; Aprilina Susandini (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
This study aims to determine the fundamental and technical analysis of stock price movements between before and during the covid-19 pandemic in banking companies listed on the Indonesia Stock Exchange (IDX).The approach used in this research is quantitative research. The total population used is 15 banking companies that are included in the infobank index15 of the Indonesia Stock Exchange. The sampling technique used was purposive sampling so that 9 banking companies were selected as samples. The variables used in this study include Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Return On Equity (ROE), Return On Assets (ROA), Operating Costs to Operating Income (BOPO), and Earning Per Share (EPS) as a company's fundamental analysis tool, and stock price and trading volume variables as a company's technical analysis tool. Based on research that has been carried out through hypothesis testing using the paired sample t-test, the results show that there are significant differences in LDR, ROA, ROE, BOPO, and stock prices of banking companies between before and during the covid-19 pandemic. Meanwhile, in CAR, EPS and trading volume of banking companies, no significant differences were found between before and during the covid-19 pandemic.